The Declension of the Feminine Gender Nouns in the Lithuanian Statute of 1588 - Ктиторова, Татьяна (Kalbotyra, 1983)
The article deals with declension types of the feminine gender nouns represented in the Lithuanian Statute of 1588. The Statute language reflects the tendency to levelling the system of the feminine gender noun forms according to the strong type of declension that corresponds to the norm orientated to the colloquial language.